Study on Weight Loss and Development of a Respiration Rate Model of Sapote Fruit (Achras sapota L) Under Hypobaric Storage - Hawa, La Choviya (Jurnal Teknologi Pertanian, 2005)
The objective of this research was to develop a model of O2 respiration rate of Sapote Fruit (Achras sapota L.) stored under a pre-determined hypobaric condition, followed by a validation test and sensitivity analysis of the developed model in relation to quality deterioration as expressed by the loss of weight of the fruit. The fruit was stored for 10 days at a various levels of combination of temperature and pressure. The temperature levels applied were 10° C and 20° C, and under a pressure of 30, 50 and 70 kPa respectively. It was observed that the fruit stored at 10° C under a pressure level of 30 kPa had the lowest initial respiration rate (9.571 mg O2/kg-jam) and weight loss i.e 3.57%. The model of respiration rate of the fruit, applicable to the above pre-determined condition, may be expressed as:   Key words: hypobaric storage, respiration rate, sapote fruit